The prognostic value of demyelinating electrophysiologic findings and cerebrospinal fluid protein levels in acute inflammatory demyelinating polyneuropathy - TUNÇ, Abdulkadir; TEKEŞİN, Aysel; GÜZEL, Vildan; ÜNLÜBAŞ, Yonca; SEFEROĞLU, Meral (Arquivos de Neuro-Psiquiatria, 2020)
Background: Guillain-Barre syndrome is an acute immune-mediated polyneuropathy characterized by rapidly evolving symptoms and disability. Cerebrospinal fluid analysis and electrophysiological studies are crucial in the diagnosis of this syndrome. Objective: To evaluate the prognostic value of the type and number of demyelinating findings and cerebrospinal fluid protein levels in patients with acute inflammatory demyelinating polyneuropathy. Methods: We retrospectively analyzed electrophysiological data and cerebrospinal fluid of 67 consecutive patients with acute inflammatory demyelinating polyneuropathy from Istanbul, Turkey (2011-2019) studied ≤ 24 hours post-onset. Results: The patients who met a higher number of demyelinating criteria had increased disability scores in the first day and first month, and higher cerebrospinal fluid protein levels were correlated with worse prognosis both on the first day and the first month. However, the disability scores did not correlate with any single specific criterion, and no significant correlation was found between the number of satisfied criteria and cerebrospinal fluid protein levels. Conclusions: The number of demyelinating criteria that are met and high cerebrospinal fluid protein levels at the disease onset may be valuable prognostic markers. More systematic studies conducted with serial nerve conduction studies are required to highlight the roles of the suggested criteria in clinical practice.
Keywords: Guillain-Barre Syndrome; Prognosis; Electromyography